2011
DOI: 10.1177/0739986311427695
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Skin Color on Hispanic Women’s Perceptions of Attractiveness

Abstract: This study relies on qualitative methods to investigate Hispanic women’s skin color perceptions. The primary goal is to identify the relevance of these perceptions on their beliefs about their own physical attractiveness. Thirty-four self-identified White-Hispanic women attending a large Hispanic Serving Institution in the southeastern United States were interviewed for this study. Unlike previous research findings on Hispanic women’s skin color preferences, findings identified a “tan” skin color as preferred;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…As with race, skin tone has played a critical role in shaping the lives of people of color, both in terms of how they view themselves and in terms of how others perceive and treat them (Jones, 2013; Rondilla & Spickard, 2007). Although the body of literature on this topic is robust for African Americans and Latino/Latinas (Gullickson, 2005; Kaufman & Wiese, 2012; Quiros & Dawson, 2013; Stephens & Fernandez, 2012; Wilder & Cain, 2011; Wilkinson & Earle, 2012), it remains underdeveloped for Asians Americans. There are currently only a handful of studies that have examined the history and influence that colorism—otherwise known as a form of prejudice or discrimination that is based on the reified social meanings attached to skin tone (Hunter, 2008)—has had within the Asian American community.…”
Section: The Skin Tone Continuummentioning
confidence: 99%
See 1 more Smart Citation
“…As with race, skin tone has played a critical role in shaping the lives of people of color, both in terms of how they view themselves and in terms of how others perceive and treat them (Jones, 2013; Rondilla & Spickard, 2007). Although the body of literature on this topic is robust for African Americans and Latino/Latinas (Gullickson, 2005; Kaufman & Wiese, 2012; Quiros & Dawson, 2013; Stephens & Fernandez, 2012; Wilder & Cain, 2011; Wilkinson & Earle, 2012), it remains underdeveloped for Asians Americans. There are currently only a handful of studies that have examined the history and influence that colorism—otherwise known as a form of prejudice or discrimination that is based on the reified social meanings attached to skin tone (Hunter, 2008)—has had within the Asian American community.…”
Section: The Skin Tone Continuummentioning
confidence: 99%
“…The omission of skin tone as a relevant predictor variable may be due in large part to the fact that most dating websites do not solicit from their users this specific piece of descriptive information. Nevertheless, research has consistently shown that skin tone impacts social outcomes such as one’s perception of attractiveness (Hill, 2002; Jones, 2013; Stephens & Fernandez, 2012), racial identity formation and self-esteem (Coard, Breland, & Raskin, 2001; Cunningham, 1997), and within-group prejudice and discrimination (Chavez-Duenas, Adames, & Organista, 2014; Rondilla & Spickard, 2007). By not collecting and analyzing these types of data, questions surrounding the influence of skin tone on mate selection remain either understudied or not studied at all.…”
mentioning
confidence: 99%
“…Moreover, since skin tone is a marker of Latin identity, studies found that compared to medium-skinned groups, lighter skinned Latinas longed to feel accepted in Latinx communities (Stephens & Fernández, 2011), but felt estranged after experiences of in-group rejection (López, Walker, & Spinel, 2015). Therefore, lighter skinned Latinas may harbor higher anti-Latinx sentiments (i.e., internalized racism).…”
Section: Social Psychological Underpinnings Of Out-group and In-groupmentioning
confidence: 99%
“…55,[59][60][61][71][72][73]85 With additional resources, future studies could also consider a longitudinal design, with time-specific data collected on when readership and health risks occurred; this would allow for a comprehensive assessment of the direction of the relationship between readership and health risks.…”
Section: Implications For Future Studiesmentioning
confidence: 99%
“…Drawing from intersectionality theory, 70 these conversations must intersect with other critical conversations about all factors impacting identity, such as race, class, and disability. [70][71][72][73] These conversations must start in grade and middle school, within the context of successful prevention programs, such as Safe Dates, which targets abuse prevention through healthy relationship skills training and gender role examination, 47,74 or Coaching Boys into Men, which trains high school coaches to have discussions with male athletes about stopping violence against women. 75 Within ongoing conversations and prevention efforts, incorporating material from popular media, such as the messages conveyed in Fifty Shades 12-14 along with hypersexualized representation of women and girls in print and visual media, is essential to address underlying issues that place women and young girls at risk of unhealthy relationships.…”
Section: Study Limitationsmentioning
confidence: 99%